Mycenaeans up to date: the archaeology of the North-Eastern Peloponnese : current concepts and new directions - Schallin, Ann-Louise; Turnabitu, Iphigeneia (Skrifter, 2015)
This volume contains the proceedings of the conference Mycenaeans up to date: The archaeology of the north-eastern Peloponnese - current concepts and new directions, which was held 10-16 November 2010, under the auspices of the Swedish Institute at Athens. The published papers reveal the latest news in the field of Mycenaean archaeology in the Argolid and the surrounding areas. Ongoing fieldwork, as well as new interpretations of the extant archaeological material is presented and discussed in detail. The first part of the volume consists of papers dealing with new, unpublished evidence regarding many of the well-known Argive sites, including Mycenae, Tiryns, Argos, Midea, and the Nemea Valley, among others. The second part is devoted to in-depth studies on a number of major themes, such as Mycenaean architecture, administration, mortuary practices and religion
"This volume presents the proceedings of the conference, entitled 'Mycenaeans up to date: the archaeology of the NE Peloponnese - current concepts and new directions', which was held in Athens between the 10th and the 14th of November 2010, under the auspices of the Swedish Institute at Athens and the University of Thessaly."
Keywords: Peloponnesus (Greece : Peninsula) -- Antiquities -- Congresses; Konferenzschrift -- 10.11.2010-16.11.2010 -- Athen; Archäologie; Mykenische Kultur; Peloponnes